A Case Report of Acupuncture Treatment on Antiphospholipid Syndrome Complicated by Cerebral Infarction - Chaoji XU; Jian ZHENG (康复学报)
Objective:To observe the clinical effect of acupuncture treatment on antiphospholipid syndrome (APS) complicated by cerebral infarction.Methods:A 28-year-old female presented in a critical condition with bilateral middle cerebral artery (MCA) thrombosis caused bilateral MCA occlusion and large areas of acute cerebral infarct in both hemispheres, on a background of APS. The patient was treated with acupuncture to promote consciousness restoration, reduce intracranial pressure and decrease brain oedema. In total, the patient underwent 24 session of acupuncture along with regular therapies.Results:After four acupuncture sessions, the patient regained spontaneous breathing, weaned off mechanical ventilation subsequently and successfully extubated. The patient had returned to her baseline level of conscious and was found to have a full neurological recovery after 24 acupuncture sessions.Conclusion:Preferable outcomes can be achieved with acupuncture treatment in patients with APS complicated by cerebral infarction.